Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/371938
|View full text |Cite
|
Sign up to set email alerts
|

Does the Diabetic Foot Have a Significant Impact on Selected Psychological or Social Characteristics of Patients with Diabetes Mellitus?

Abstract: The aim of our case-control study was to compare selected psychological and social characteristics between diabetic patients with and without the DF (controls). Methods. 104 patients with and 48 without DF were included into our study. Both study groups were compared in terms of selected psychosocial characteristics. Results. Compared to controls, patients with DF had a significantly worse quality of life in the area of health and standard of living as shown by lower physical health domain (12.7 ± 2.8 versus 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 34 publications
(43 reference statements)
5
55
0
11
Order By: Relevance
“…42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionsupporting
confidence: 77%
“…12 Lack of disabled access and facilities may impede social activity and patients may feel guilty about imposing on the lives of friends or family. 13 More depression and poorer psychosocial adjustment by DM patients with DFU compared to those without has been shown in early 14 and recent 15 studies. In general, adverse psychological effects associated with DFU include a sense of loss of self, social isolation, 16 loss of self-esteem, fear, anger, helplessness, and depression.…”
Section: Introductionmentioning
confidence: 94%
“…One group has reported that first ulcers are associated with depression and that this is independently associated with mortality at 5 years (52). Others, however, have reported that both quality of life and depressive symptoms are reversed by healingdeither with or without amputation (53)(54)(55). Wukich et al (56) have recently reported that people with diabetic foot disease fear major amputation more than they fear death.…”
Section: Improving Well-being: the Patient Agendamentioning
confidence: 99%
“…Many studies suggest that diabetic foot greatly affects patients' physical health . Several studies reported that diabetic foot has a negative effect on patients' daily, social, leisure, and family lives . In addition, another study showed that it not only affects physical health but also has psychological and emotional effects .…”
Section: Introductionmentioning
confidence: 99%